Assessing the Effect of Green Supply Chain Management on the Triple Bottom Line at McDonald's Bandung - Muhamad Rafli; Maya Irjayanti (International Journal of Islamic Business and Management Review, 2025)
The development of the fast food industry, particularly McDonald's in Bandung, has had a significant impact on the environment due to the use of plastic packaging and production waste. With increasing awareness of sustainability issues, companies have begun adopting Green Supply Chain Management (GSCM) practices to mitigate these negative impacts. GSCM focuses not only on environmental aspects but also on economic and social performance, as reflected in the Triple Bottom Line (TBL) concept. This study aims to analyze the effect of GSCM implementation on TBL at McDonald's in Bandung, given the limited number of similar studies in Indonesia, particularly in the fast food sector. This study aims to: 1) test the positive effect of GSCM on TBL, 2) empirically determine the strength of organizational culture's influence in strengthening the relationship between GSCM and TBL, and 3) empirically determine the strength of organizational size's influence in strengthening the relationship between GSCM and TBL. This study used a quantitative approach with a survey method of 184 McDonald's employees in Bandung selected through purposive sampling. Data were collected through an ordinal-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test validity, reliability, and relationships between variables. The study variables included GSCM (dimensions of internal management, green design, and green production), TBL (economic, social, and environmental performance), organizational size, and organizational culture. The results showed that GSCM had a significant positive effect on TBL. This finding aligns with McDonald's efforts to implement environmentally friendly policies, such as reducing plastic waste and using recycled materials, which have been shown to support business sustainability. This study provides practical contributions for businesses optimizing GSCM strategies to achieve sustainability, as well as academic contributions by enriching the literature on GSCM in the fast food industry. Suggestions for further research include expanding the sample to more diverse geographic regions and exploring mediating variables such as technological innovation to deepen the analysis.